Análisis del proceso de contratación en el Almacén Viviana de la Parroquia Isla de Bejucal - Cerezo Alvarez, Katherine Xiomara (2021)
The present case study seeks to carry out an analysis of the contracting process in the Viviana warehouse of the Isla de Bejucal parish under the objective of investigating the contracting process carried out in the Viviana Warehouse located in the Isla de Bejucal Parish. The importance of a personnel selection process for adequate hiring is emphasized, processing this through a series of relevant topics for scientific investigation, finally allowing an analysis of the case that is the store or commercial sales of electrical appliances, and thus be able to be carried out. To argue with qualitative quantitative data the results of the case study, since that is where it was evidenced that in the warehouse there is no adequate method of contracting, since it is a merely family business, the hiring of personnel is by solidarity of family members, now it could be concluded that In micro-enterprises, the existence of a personnel selection process is necessary, since like any enterprise, it seeks to grow and, therefore, acquire greater knowledge in administrative processes, in order to be able to select suitable personnel and thus improve the Viviana warehouse administration, in order that the objectives of s us owners, that is, improve the profitability of the business.